2007
DOI: 10.1021/nl070678d
|View full text |Cite
|
Sign up to set email alerts
|

Nanosize and Vitality:  TiO2 Nanotube Diameter Directs Cell Fate

Abstract: We generated, on titanium surfaces, self-assembled layers of vertically oriented TiO2 nanotubes with defined diameters between 15 and 100 nm and show that adhesion, spreading, growth, and differentiation of mesenchymal stem cells are critically dependent on the tube diameter. A spacing less than 30 nm with a maximum at 15 nm provided an effective length scale for accelerated integrin clustering/focal contact formation and strongly enhances cellular activities compared to smooth TiO2 surfaces. Cell adhesion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

61
1,022
5
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,156 publications
(1,094 citation statements)
references
References 26 publications
61
1,022
5
6
Order By: Relevance
“…In addition, the typical calibrated voltages recorded in our measurements are similar to or greater than the largest values reported previously. The improvement in peak amplitude is consistent with the fact that the nanodevices protrude from the plane of substrate and hence can increase NW/cell interfacial coupling (17,(24)(25)(26)(27)(28) and with our previous studies of cultured neurons (14) and embryonic hearts (15). Recent studies using top-down fabricated NWs also reported millivolt-scale signals, although the cardiomyocytes in this case appeared morphologically undeveloped (e.g., Ϸ10-mdiameter spherical structures), and thus it is difficult to compare these results directly with our work and previous planar FET studies.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, the typical calibrated voltages recorded in our measurements are similar to or greater than the largest values reported previously. The improvement in peak amplitude is consistent with the fact that the nanodevices protrude from the plane of substrate and hence can increase NW/cell interfacial coupling (17,(24)(25)(26)(27)(28) and with our previous studies of cultured neurons (14) and embryonic hearts (15). Recent studies using top-down fabricated NWs also reported millivolt-scale signals, although the cardiomyocytes in this case appeared morphologically undeveloped (e.g., Ϸ10-mdiameter spherical structures), and thus it is difficult to compare these results directly with our work and previous planar FET studies.…”
Section: Resultssupporting
confidence: 74%
“…A unique feature of these studies compared with conventional planar devices measurements is that the nanodevices protrude from the plane of substrate, and hence can increase NW/cell interfacial coupling. Indeed, studies have shown that nanostructured interfaces can enhance cellular adhesion and activity (17,(24)(25)(26)(27)(28), and thus it is likely that NW and CNT devices have an intrinsic advantage for building interfaces to cells and tissue.…”
mentioning
confidence: 99%
“…Culturing human mesenchymal stem cells (MSCs) on a range of nanotubes with diameters between 30 and 100 nm, cell stretching and expression of osteogenic differentiation markers was highest on 100-nm nanotubes, whereas cell-adhesion rates increased with decreasing tube diameter, with a maximum at 30 nm. This finding is particularly striking in light of previous contrary reports showing that nanoscale-dependent differentiation of MSCs to osteoblasts followed in the opposite direction (2,3). In these studies, data were presented showing that not only adhesion, proliferation, and migration, but also osteogenic differentiation of rat bone marrow MSCs were highest on 15-nm nanotubes and decreased dramatically on 70-and 100-nm nanotubes.…”
mentioning
confidence: 69%
“…In addition, modifying the natural oxide layer of titanium, which provides remarkable surface properties, can address issues related to insufficient osseointegration [6] and undesired cell growth [7][8][9]. Titanium dioxide nanotubes (TNT) made by electrochemical anodization can modify the oxide layer, which can be utilized to positively affect cellular behaviours, such as migration [9], adhesion [10], proliferation [7,10,11] and differentiation [12,13]. By modifying the surfaces of SPD processed titanium with TNT layers, there is a possibility to simultaneously increase the bulk and surface properties, therefore further increasing the success rate of titanium implants.…”
Section: Introductionmentioning
confidence: 99%